Konsep Kesatuan Tema al-Qur’an Menurut Sayyid Qutb - Siti Mulazamah (JOURNAL OF QUR'AN AND HADITH STUDIES, 2014)
This article is to prove that the more comprehensive the interpretation of the Qur’an is the more objective his/her interpretation is. This article demonstrates that Sayyid Qutb is one of the mufassirs who interprets the Qur’an comprehensively. The concept offered by Qutb is the thematic unity of the Qur’an. Qutb’s interpretation is based on the thematic unity in the Qur’an as a whole and in its each Sura. This article agrees with Muhammad ‘Abd Allah Diraz, A.H. Mathias Zahniser who argue for the harmony, coherence and thematic unity of the Qur’an. However, it argues against ‘Izzuddin ibn ‘Abd al-Salam, Subhi al-Salih, and Salwa M.S. El-Awa who doubt and deny the harmony, coherence and thematic unity of the Qur’an.